2009
DOI: 10.1021/ie901062c
|View full text |Cite
|
Sign up to set email alerts
|

Study on Several Mesoporous Materials Catalysts Applied to the Removal of Trace Olefins from Aromatics and Commercial Sidestream Tests

Abstract: Deep removal of trace olefins from aromatics using mesoporous materials and modified mesoporous materials was studied with regard to the removal of trace olefins from aromatic hydrocarbons. The mesoporous materials and the modified mesoporous molecular sieve materials were characterized by X-ray diffraction and Fourier transform infrared (FT-IR) spectroscopy. Under the commercial sidestream test, the effects of four types of mesoporous materials, with regard to the removal of olefins from the aromatics, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…The distance between layers of bentonite can be determined based on the position of the characteristic reflection peak (001) in the XRD patterns. In Figure 2a, the XRD pattern of Bent had a characteristic (001) reflection at approximately 7.10° (2θ) [25], while the peak position shifted to 5.51° (2θ) after Bent was modified with PAA. Results calculated by the Bragg equation showed that the shift in the distance between layers was from 1.24 nm (Bent) to 1.60 nm (Bent-PAA) when Bent was modified with PAA.…”
Section: Resultsmentioning
confidence: 99%
“…The distance between layers of bentonite can be determined based on the position of the characteristic reflection peak (001) in the XRD patterns. In Figure 2a, the XRD pattern of Bent had a characteristic (001) reflection at approximately 7.10° (2θ) [25], while the peak position shifted to 5.51° (2θ) after Bent was modified with PAA. Results calculated by the Bragg equation showed that the shift in the distance between layers was from 1.24 nm (Bent) to 1.60 nm (Bent-PAA) when Bent was modified with PAA.…”
Section: Resultsmentioning
confidence: 99%
“…Clay is known to be a highly versatile material due to its widely known applications in various industries, many of which are shown in Fig. 1 7,15‐26 …”
Section: Introductionmentioning
confidence: 99%
“…1. 7,[15][16][17][18][19][20][21][22][23][24][25][26] The olefin content of a hydrocarbon stream is measured with its Bromine Index (BI) in accordance with ASTM D 2710-92 standard. 27,28 The BI corresponds to the bromine milligrams consumed by a 100 g liquid hydrocarbon sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These olefins must be removed for their negative effect on the following process. Clay treatment have been widely used for removing trace olefins from aromatics 20 with the drawbacks of limited lifetime and the used clay could not reuse except discard as solid waste. A growing awareness of environmental protection in the chemical industry asks for finding an efficient and cost-effective method to remove olefins in aromatics.…”
Section: Introductionmentioning
confidence: 99%